The effect of financial literacy on online loans and its impact on poverty - Irma Yunita Irma; Enjat sudrajat; Nono Arief Rachman; Bachtiar Rifai (International Journal of Applied Finance and Business Studies, 2023)
The development of information technology has brought things in a simpler direction, one of which is related to banking financial technology where banking transactions that were originally done offline can now be done online. Likewise transactions that are currently life, namely loans made online orpeer to peer lending.This study uses secondary data for 2019 and 2022 using Soft SEM-Pls and structural methods. The results of the study partially state that financial literacy has an effect on interest in online loans and financial literacy has an effect on poverty rates. The results of this study also found There is an influence of interest in online loans on poverty rates. However, the research results also show that interest in online loans has no effect on the poverty rate. This research provides valuable knowledge that online loans do not have a major impact on reducing poverty.